Synthesis, anticonvulsant activity and in silico study of some novel amino acids incorporated bicyclo compounds (Stamford Journal of Pharmaceutical Sciences, 2010)
In  the present study, some novel amino acids incorporated bicyclo compounds have been synthesized and their structure was confirmed by physico-chemical and spectral data. The title compounds were evaluated for in silico toxicity study and anticonvulsant activity by maximal electric shock method. The results showed that substitution with cysteine and glutamic acid moiety was found to increase the activity. In silico toxicity study results showed that the compounds are free of toxicity in neurotoxicity, irritability, sensitivity, immunotoxicity and oncogenecity  Key words: Maximal electrical shock method; anticonvulsant activity; in silico toxicity. DOI: 10.3329/sjps.v2i2.2607Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 42-47